I have tried a little bit to solve the problem which goes as follows:

My intuition says that there exist no $f:\Bbb R\to\Bbb R$ such that $$f(g(x))=x^{2018}\text{ and }g(f(x))=x^{2019}.$$

Note that $$f(g(f(x)))=f(x)^{2018}\implies f(x^{2019})=f(x)^{2018}$$

Similarly, $$g(x^{2018})=g(x)^{2019}$$ Putting $x=1$ in $f(x^{2019})=f(x)^{2018}$, we get $f(1)=f(1)^{2018}$ and thus $f(1)=0$ or $f(1)=1$.

Similarly, putting $x=1$ in $g(x^{2018})=g(x)^{2019}$ we get $g(1)=g(1)^{2019}$ and thus $g(1)=0,1,-1$.

Now, I can't proceed further. Can anybody solve it? Thanks for assistance in advance.


2 Answers 2


Here is a simple proof (to avoid confusion I will write $f^{y}(x)$ instead of $f(x)^{y}$):

Suppose that there are two such functions $f,g$ as in your question.

Note that $\forall\space i \in\{-1, 0, 1\}$, we have $f(i^{2019}) = f(i) = f^{2018}(i)$ and thus $\label{*}\tag{*} f(i) \in \{0, 1\} \quad\forall\space i \in\{-1, 0, 1\}.$

On the other hand, since $g(f(x)) = x^{2019} \space\forall x\in\mathbb{R}$,

  • $g(f(1)) = 1$,
  • $g(f(0)) = 0$,
  • $g(f(-1)) = -1$.

This is impossible since $f$ (and thus also $g\circ f$) only takes two (or fewer) values on $\{-1, 0, 1\}$ after \eqref{*}. $\Longrightarrow\Longleftarrow\quad\square$


Another classic trick that can be used here is that there is a bijection between the set of fixed points of $fg$ and fixed points of $gf$. If $x$ is such that $f(g(x))=x$ then $g(f(g(x)))=g(x)$ so $g(x)$ is a fixed point of $gf$. Similarly whenever $y$ is a fixed point of $gf$, we can show that $f(y)$ is a fixed point of $fg$. Convince yourself that on the sets of fixed points, this gives a bijection.

Can you see why the $fg$ and $gf$ you've been given fail this condition?


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.